Enhancing mushroom production using physical treatments prior to fruiting body formation - Roshita Ibrahim; Nor Farha Liyana Yasin; Adzemi Mat Arshad; Sayed Mohamed Zain Sayed Hasan (Penerbit Universiti Kebangsaan Malaysia, 2015)
There is an increasing world demand for mushrooms as their culinary uses and nutritional benefits become more widely known. The grey oyster mushroom (Pleurotus sajor-caju) is an edible mushroom commercially cultivated in Malaysia. In this study, the effects of high sound intensity, bright light, low temperature (5°C) and electrical shock on the growth, yield and physico-chemical properties of the mushroom was investigated. The results showed that mushroom cultures treated with bright light, high sound intensity and cold temperature produced spawn more rapidly, requiring a shorter time for the mycelium to fill up the substrate bag as compared with the control. An electric shock was observed to be the most effective treatment that promoted the earliest emergence of pinheads and formation of fruiting bodies. Besides, mushroom treated with electrical shock treatment showed higher yield which was twice more compared to control. For the color of the mushroom, cold treatment showed the lightest color with the highest yellow intensity (b* value) compared to other treatments, whilst mushroom without any physical treatment had the highest red intensity (a* value). Different physical treatments applied did not show any significant effect on texture, moisture, ash, protein and crude fiber contents. In conclusion, among all the physical treatments, electrical shock was the best treatment as it took a shorter spawning time with the greatest yield of mushroom production.